2022
DOI: 10.1155/2022/2235994
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Cardiac Ultrasound Index and Cardiovascular Risk in Healthy Obese and Overweight Populations

Abstract: Objective. To investigate the correlation of obesity and overweight with cardiac ultrasound parameters and future cardiovascular risk among healthy populations. Methods. Basic clinical characteristics as well as cardiac ultrasound parameters were collected from healthy people. Firstly, all participants were divided into three groups: normal, overweight, and obese. Then the differences in cardiac ultrasound parameters between the three groups were calculated. Subsequently, those aged 35–60 years were screened t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The high prevalence of this marker is intertwined with the prevalence of obesity and overweight, resulting in a higher rate among men than women. 42 Aortic dilatation and left atrial enlargement were also incidentally observed and are closely related to the prevailing hypertension. However, it is worth noting that merely 0.54% of the populace had coronary stents fitted - A figure somewhat lower than anticipated, which may correlate to insufficient identification through ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of this marker is intertwined with the prevalence of obesity and overweight, resulting in a higher rate among men than women. 42 Aortic dilatation and left atrial enlargement were also incidentally observed and are closely related to the prevailing hypertension. However, it is worth noting that merely 0.54% of the populace had coronary stents fitted - A figure somewhat lower than anticipated, which may correlate to insufficient identification through ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial positive connection between a number of cardiac ultrasound parameters and cardiovascular risk was found in our prior work. 21 We aimed to investigate the association between NHR and cardiac ultrasound parameters in the current investigation. The findings suggested a link between high NHR and early structural alterations in the heart since the high NHR population had higher levels of AO, LA, RA, RV, ESD, EDD, MPA, RVOT, IVS, and LVPW than the low NHR population.…”
Section: Discussionmentioning
confidence: 99%
“…EAT and the associated increased fibrosis could anatomically disrupt the cell-to-cell electrical conduction of cardiomyocytes, which might result in slow conduction, facilitating arrhythmogenesis. Obesity and overweight slightly increased the RVOT diameter [92]. RVOT, commonly covered with EAT, is vital for ventricular arrhythmia genesis [93].…”
Section: Obesity/epicardial Adipose Tissue (Eat) Accumulation In the ...mentioning
confidence: 99%
“…EAT and the associated increased fibrosis could anatomically disrupt the cell-to-cell electrical conduction of cardiomyocytes, which might result in slow conduction, facilitating arrhythmogenesis. Obesity and overweight slightly increased the RVOT diameter [92]. RVOT, commonly covered ) current (I Ca-L ) and a rapid component of delayed rectifier potassium current (I Kr-tail ) and a larger late sodium (Na + ) current (I Na-Late ) than RV apex myocytes, which prolongs action potential duration (APD).…”
Section: Obesity/epicardial Adipose Tissue (Eat) Accumulation In the ...mentioning
confidence: 99%